Novelty-seeking behaviors and the escalation of alcohol drinking after abstinence in mice are controlled by metabotropic glutamate receptor 5 on neurons expressing dopamine D1 receptors - Rodriguez-Parkitna, Jan; Sikora, Magdalena; Gołda, Sławomir; Gołembiowska, Krystyna; Bystrowska, Beata; Engblom, David; Bilbao, Ainhoa; Przewlocki, Ryszard (Biological psychiatry, 2013)
Background - Novel experiences activate the brain's reward system in a manner similar to drugs of abuse, and high levels of novelty-seeking and sensation-seeking behavior have been associated with increased susceptibility to alcohol and drug abuse. Here, we show that metabotropic glutamate receptor 5 (mGluR5) signaling on dopaminoceptive neurons is necessary for both novelty-seeking behavior and the abstinence-induced escalation of alcohol drinking. - Methods - Mice harboring a transgene expressing microRNA hairpins against mGluR5 messenger RNA under the control of the D1 dopamine receptor gene promoter (mGluR5KD-D1) were tested in a battery of behavioral tests measuring learning abilities, anxiety levels, reactions to novelty, operant sensation seeking, and alcohol sensitivity. In addition, we have developed a method to assess long-term patterns of alcohol drinking in mice housed in groups using the IntelliCage system. - Results - mGluR5KD-D1 mice showed no behavioral deficits and exhibited normal anxiety-like behaviors and learning abilities. However, mGluR5KD-D1 animals showed reduced locomotor activity when placed in a novel environment, and exhibited decreased interaction with a novel object. Moreover, unlike control animals, mutant mice did not perform instrumental responses under the operant sensation-seeking paradigm, although they learned to respond for food normally. When mGluR5KD-D1 mice were provided access to alcohol, they showed similar patterns of consumption as wild-type animals. However, mutant mice did not escalate their alcohol consumption after a period of forced abstinence, but control mice almost doubled their intake. - Conclusions - These data identify mGluR5 receptors on D1-expressing neurons as a common molecular substrate of novelty-seeking behaviors and behaviors associated with alcohol abuse.